Increasing the Learning Outcomes of Class V Students in Social Sciences Subjects Through Cooperative Learning Type Student Teams Achievement Division (STAD) at SD Negeri Malengu, Gowa Regency - Supardi Salam (International Journal of Education, Vocational and Social Science, 2024)
The problem in this research is how to improve the learning outcomes of class V students in social studies subjects through the implementation of STAD type cooperative learning at Malengu State Elementary School, Gowa Regency? The aim of this research is to describe the improvement in learning outcomes of class V students in social studies subjects through STAD type cooperative learning at SD Negeri Malengu, Gowa Regency. The approach used is a qualitative approach. The type of research used is classroom action research which consists of two cycles, each cycle consisting of two meetings, with activity procedures including planning, implementation, observation and reflection. Data collection using observation, test and documentation techniques. The subjects in this research were 1 teacher and all class V students at SD Negeri Malengu, Gowa Regency, a total of 31 students consisting of 15 boys and 16 girls in the 2023/2024 academic year in the odd semester. Meanwhile, the data is explained descriptively by describing the learning process for each cycle. The research results showed that there was an increase in student learning outcomes after implementing STAD type cooperative learning, from the sufficient category with an average score of 63.7 in cycle I to the high category with a score of 83.3 in cycle II. Teachers' teaching activities increased from the medium category to the high category, so that STAD type cooperative learning had an impact on improving student learning outcomes in social studies subjects.